Impact of Information Technology Towards Organizational Performance - Omar, Ariff Othman; Jailani, Sri Fatiany Abdul Kader; Ali, Syukrina Alini Mat; Yunus, Noor’ain Mohamad (Advances in Social Sciences Research Journal, 2023)
Since the beginning of the 21st century, numerous organizations have extensively implemented information technology into their operations. With regard to this, it captures the interest of researchers, practitioners, academicians, and policymakers to comprehend the role of organization dynamic capability in information technology and the role of digital leadership in enhancing organizational performance and enabling the information technology process. There was limited study on the impact of technology on the performance of government agencies. Therefore, this research focuses on government agencies in Malaysia. This study was conducted to seek the true role of information technology in organizational performance and the impact of information technology on organizational performance. Through an analysis of the 131 randomly selected workers, this paper investigates the impact of information technology on organizational performance. This study examines the effects of IT Operation, IT Knowledge, and IT Competence on the performance of an organization. In this research, SPSS was used for normality and reliability analysis, as well as descriptive organization multiple regression analysis. The result revealed that only IT Competence has a positive impact on organizational performance. The finding also revealed that the impact of information technology on the performance of an organization is minimal and contributes a minor impact.